2014
DOI: 10.5296/rae.v6i2.5226
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Financial Development and Economic Growth in Africa

Abstract: This study examines the relationship between financial development and economic growth. It presents evidence on a cross section of 50 African countries whose data is available for the period 1980-2008. Two proxies of financial development are employed: the ratio of credit to the private sector to total GDP and the ratio of broad money (M2) to total GDP. We establish a positive relationship between financial development and economic growth. However, we find that the relationship between private sector credit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…The financial development was represented by two different measuring variables, broad money (M2) to GDP ratio and private sector credit (PSC) to the GDP of the respective years. The broad money to GDP (M2/GDP) ratio is the most regularly used measure of FD (Musamali et al, 2014;Badeeb and Lean, 2017). Likewise, the National Bank of Ethiopia ( 2019) explained that the ratio of broad money to the GDP (M2/GDP) is an important financial deepening indicator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The financial development was represented by two different measuring variables, broad money (M2) to GDP ratio and private sector credit (PSC) to the GDP of the respective years. The broad money to GDP (M2/GDP) ratio is the most regularly used measure of FD (Musamali et al, 2014;Badeeb and Lean, 2017). Likewise, the National Bank of Ethiopia ( 2019) explained that the ratio of broad money to the GDP (M2/GDP) is an important financial deepening indicator.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, if M2/GDP increases by 1%, the FDI inflow towards this country increases by 0.85%. The larger value of the M2 to GDP ratio indicates a higher level of FD in a country (Musamali et al, 2014). It implies that higher FD, measured as M2/GDP, is among the important attracting forces of FDI.…”
Section: The Long-run and Short-run Analysismentioning
confidence: 99%
“…(2011), the results of their work advocated a feedback effect between the financial sector and economic growth for most of the emerging regions. Musamali and al. (2014) examined the relationship between financial development and economic growth in 50 African countries for the period 1980-2008.…”
Section: Feedback Effect: a Two-way Causal Relationship Between Finanmentioning
confidence: 99%
“…The findings revealed that financial intermediation has a significant impact on economic growth in Nigeria. Musamali, Nyamongo, and Moyi (2014) examined the relationship between financial development and economic growth from 50 African countries for period 1980-2008. The result found that there was a positive relationship between financial development and economic growth.…”
Section: Introductionmentioning
confidence: 99%